Developing Jamu-Based Educational Tourism in Kiringan Hamlet, Bantul Regency, Yogyakarta - Nurlena Nurlena (Journal of Business on Hospitality and Tourism, 2015)
Kiringan Hamlet, located in Bantul Regency, is the only jamu-producing hamlet in Yogyakarta. The hamlet produces jamu (traditional herbal medicine) and sells the products traditionally. Almost a half of the hamlet’s population have skill to make jamu. Based on this fact, the hamlet’s existence gives hope for further development as an alternative tourist destination, especially in Yogyakarta.Therefore, this study was aimed at identifying the tourism potential in Kiringan Hamlet as well as processing it as a strategy for tourism development. This study was a descriptive study so that the data in this study was obtained by conducting interviews with local community, village officials, and tourism office staffs, field observation and literature study. The SWOT analysis results suggested that Kiringan Hamlet deserved quite high potential for serving as a jamu-based educational tourism site.Based on this quite high development potential, this paper then proposed the tourism development plan to be executed by the existing stakeholders so that this study could have significant implications for the efforts to develop tourism in the hamlet.